Cooperative RIS and Relaying IoV Networks: A Deep Study on Position Analysis. (9th June 2022) - Zhu, Jiaxing; Zhang, Guoan; Jiang, Yan; Duan, Wei; Ou, Jianghong; Fan, Dahua
Abstract : In this paper, a hybrid relay- and reconfigurable intelligent surface- (RIS-) assisted cooperative communication system is proposed. Considering the overall user position referring to the reflective RIS, the downlink propagation can be summarized as two cases: for the first case, the mobile user can only be assisted by the relay (on the back of RIS); for the second case, the mobile user will be assisted by both of the RIS and relay. In our proposed system, a novel concept named "balance position" is investigated, which can be used to resolve specific deployment issue of the RIS. Due to the difficulty of obtaining the closed-form expressions of the achievable capacity, we derive the tight upper bound for the channel gain through observing the central limit theorem (CLM) and Jensen's inequality and determine its trend for the mobile user. Numerical results verify the correctness of our analysis and superiority of our proposed scheme. Moreover, for an increasing number of RIS elements, the system capacity will be significantly improved, and the balance position will be far away from RIS.